Functional Movement Screen Detected Asymmetry & Normative Values Among College-Aged Students - Craig R Triplett; Bryan S Dorrel; Matthew L Symonds; Corey A Selland; Daniel D Jensen; Christopher N Poole (North American Sports Medicine Institute, 2021)
# Background The Functional Movement Screen (FMS™) is a popular test used by sports medicine professionals to identify dysfunctional movement patterns by analyzing mobility and stability during prescribed movements. Although the FMS™ has been a popular topic of research in recent years, normative data and asymmetries in college-aged students have not been established through research. # Purpose The objective was to determine normative FMS™ scores, report frequency counts for FMS™ asymmetries, and determine if the number of sports seasons and number of different sports an individual participated in during high school varied between university students that showed FMS™ identified asymmetries. # Study Design Cross-sectional Study # Methods One hundred university students completed the FMS™ and an associated survey to determine which sport(s) and for how many seasons they participated in each sport(s) during high school. Total FMS™ scores were assessed as well as identifying the presence of an asymmetry during a FMS™ screen. An asymmetry within the FMS™ was defined as achieving an unequal score on any of the screens that assessed right versus left movements of the body. # Data Analysis Data analysis included descriptive statistics, Pearson correlation was utilized to investigate the relationship between number of sports played and number of sport seasons. Shapiro Wilk test for normality, and Mann Whitney U test was employed to investigate group differences in number of sports played. All analyses were conducted using SPSS software. # Results Statistically significant correlations (r = .286, r^2^ = .08, p < 0.01) were found for both number of sport seasons and number of sports with FMS™ total score. In addition, participants without FMS™-detected asymmetries played significantly more seasons and more sports than their peers that presented asymmetries (U = 946.5, z = -1.98, p = 0.047). Finish with the actual p-value in parenthesis. # Conclusion Participating in multiple sports and multiple sport seasons during high school was associated with higher FMS™ total scores. Results suggest that participating in multiple sports and multiple sport seasons was associated with fewer asymmetries, which may decrease subsequent injury risk. # Level of Evidence 3b